Flipped Classroom Implementation: A Case Report of Two Higher Education Institutions in the United States and Australia. Issue 1 (2nd January 2016) - McLaughlin, Jacqueline E.; White, Paul J.; Khanova, Julia; Yuriev, Elizabeth
Abstract: This case report explored the implementation of flipped classrooms at two higher education institutions. Experiences and publications from the institutions were used to identify and describe common themes, including successes and challenges encountered along with potential solutions to common misalignments, particularly as related to technology-enhanced learning. Strategies for selecting and delivering pre-class content, designing and implementing in-class activities, and identifying and using assessments to inform practice are described. Overall design considerations include instructor skill development, student buy-in, and institutional support for the model. This report highlights several critical approaches to effectively designing and implementing the flipped classroom model, with consideration given to the use of technology to support this innovation.